(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article implemented an Android application-based speed and direction control of DC motor using Bluetooth module. This setup consists of two basic primary elements communicating with each other: i) Bluetooth of smartphone which is connected to the Arduino microcontroller, IC and DC Motor interfaced with a L293D motor driver IC and ii) a Bluetooth module HC-05.The android application in smartphone sends/receives data to/from the microcontroller using the Bluetooth. An android application in the smartphone acts as a display panel for the user to send/receive/view the output and input of the DC motor. The display includes a screen showing the commands and responses against each other. The motor can be rotated 0-360 degrees and can even change its direction from left to right until stopped. Thus, this proposed control methodology is applied to control speed and direction of DC motor wirelessly.